A survey on existing IP trace back mechanisms and their comparisons - Shariff, Vahiduddin; Ramya K, Ruth; Renuka Devi, B; Bhattacharyya, Debnath; Kim, Tai-hoon (International Journal of Engineering and Technology, 2018)
Security is the one of the main point of focus in recent trends of computer science, as it has to determine the right people accessing the system and ones who are trying the bypassing it. IP spoofing is one of the prevalent attacks, where the attackers launch the attack by spoofing the source address, once this happens they can attack without revealing their exact location. The attacker uses a fraudulent IP address to conceal their identity. To reveal the attackers real locations many IP trace back mechanisms have been proposed but the attacker immediately gets away with the information. There is another problem which is to detect DDoS traffic and the precarious packets set up by the attacker, which are a threat to the victim as well as the whole network, here lies another hurdle which is to differentiate between the attacker’s data traffic from the normal data traffic. There are many solutions given for this but one among them is IP trace back which already has researched upon in the past and implemented then, but what is lacking in the solution such that the attacks are even now taking place. IP trace back if modified, strengthened would analyze the traffic faster and trace out the attacker with a faster pace, which is why a hybrid IP tracing and tracking mechanism if introduced could ease the current problem.